2015
DOI: 10.1016/j.jacc.2015.05.017
|View full text |Cite
|
Sign up to set email alerts
|

2-Year Outcomes in Patients Undergoing Surgical or Self-Expanding Transcatheter Aortic Valve Replacement

Abstract: In patients with severe aortic stenosis who are at increased surgical risk, the higher rate of survival with a self-expanding TAVR compared with surgery was sustained at 2 years. (Safety and Efficacy Study of the Medtronic CoreValve System in the Treatment of Symptomatic Severe Aortic Stenosis in High Risk and Very High Risk Subjects Who Need Aortic Valve Replacement; NCT01240902).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
206
2
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 375 publications
(226 citation statements)
references
References 16 publications
8
206
2
10
Order By: Relevance
“…10,16 At 1 year, patients who underwent TAVR had significantly lower mean gradients (9.1 ± 3.5 mm Hg vs. 12.4 ± 7.4 mm Hg) and larger EOA (1.9 ± 0.5 cm 2 vs. 1.6 ± 0.5 cm 2 ) than patients who underwent SAVR. However, PWTd (11.24 ± 1.95 to 11.45 ± 1.73 mm, p = 0.159) and interventricular SWTd (12.00 ± 2.07 to 11.99 ± 1.94 mm, p = 0.954) were unchanged in the SAVR group at discharge, as well as in the TAVR group (11.19 ± 1.98 to 11.39 ± 2.05 mm; p = 0.435 and 11.97 ± 2.35 to 12.26 ± 2.41 mm; p = 0.155, respectively).…”
Section: Remodeling After Savr and Tavrmentioning
confidence: 98%
“…10,16 At 1 year, patients who underwent TAVR had significantly lower mean gradients (9.1 ± 3.5 mm Hg vs. 12.4 ± 7.4 mm Hg) and larger EOA (1.9 ± 0.5 cm 2 vs. 1.6 ± 0.5 cm 2 ) than patients who underwent SAVR. However, PWTd (11.24 ± 1.95 to 11.45 ± 1.73 mm, p = 0.159) and interventricular SWTd (12.00 ± 2.07 to 11.99 ± 1.94 mm, p = 0.954) were unchanged in the SAVR group at discharge, as well as in the TAVR group (11.19 ± 1.98 to 11.39 ± 2.05 mm; p = 0.435 and 11.97 ± 2.35 to 12.26 ± 2.41 mm; p = 0.155, respectively).…”
Section: Remodeling After Savr and Tavrmentioning
confidence: 98%
“…Należy również rozważyć TAVI u pacjentów wysokiego ryzyka z ciężką stenozą aortalną, którzy mogliby być leczeni chirurgicznie, ale w ocenie kardiogrupy (Heart Team) TAVI jest metodą preferowaną ze względu na indywidualne ryzyko i możliwości anatomiczne [495,496]. W niedawno opublikowanym badaniu u pacjentów z ciężką stenozą aortalną wykonanie TAVI z zastosowaniem samorozprężalnej protezy biologicznej wiązało się z większą przeżywalnością zarówno po roku, jak i po 2 latach [497,498].…”
Section: Stenoza Aortalnaunclassified
“…Two ongoing randomized controlled trials are specifically investigating which anti-thrombotic strategy might be best following TAVR (clinicaltrials.gov: NCT02556203-GALILEO, NCT02664649-ATLANTIS). Finally, another important observation is that most studies report a lower rate of newonset atrial fibrillation in the TAVR group as compared to the SAVR group (6)(7)(8)(9)(10)(11)(12); whether this may be associated with a lower stroke risk at medium term follow-up for TAVR patients still has to be determined. In addition, a number of other procedural complications such as acute kidney injury and major bleeding are only half as common after TAVR than SAVR (4).…”
mentioning
confidence: 99%
“…In addition, the first randomized trial comparing TAVR and SAVR in all-comer patients (NOTION) indicated that these findings also apply to patients at even lower surgical risk (8). Figure 1 gives an overview of all-cause mortality rates reported for the different randomized controlled trials comparing TAVR and SAVR (6)(7)(8)(9)(10)(11)(12). Clearly, long-term follow-up data are needed for the lower risk patient populations; however, it will just be a matter of time before these data will become available (clinicaltrials.gov: NCT02825134-NOTION-2, NCT02675114-PARTNER-3, NCT02701283-TAVRlow risk).…”
mentioning
confidence: 99%